Evaluation of the genomic diversity and shared ancestry of the Meitei community of Manipur (India) with the East Asian populations using autosomal STRs - Surendrajit Leishangthem; K. P. S. Kushwaha; Tanya Chauhan; R. K. Kumawat; Gyaneshwer Chaubey; Pankaj Shrivastava (Taylor & Francis Group, 2020)
Aim To study molecular diversity and genomic heritage of the Meitei community of Manipur using 20 autosomal gene loci markers. Subjects and methods Blood samples were collected from 120 unrelated, healthy individuals of the Meitei population following ethical standards. DNA was extracted using the Phenol chloroform organic extraction method and amplified using the PowerPlex® 21 system. Genetic profiles of the individuals were generated using the Genetic Analyser 3500XL following the recommended protocol. Results The studied population showed Observed Heterozygosity (Hobs) from 0.583 (TH01) to 0.90 (D6S1043) among all the studied loci. The discrimination power and exclusion power for all the studied loci were found to be 1 and 0.9999999988, respectively, with the maximum power of discrimination being found at Penta E locus. Conclusions All the studied loci showed a high degree of matching probability and paternity index of 2.83 × 10−24 and 7.35 × 108, respectively; these are high-level statistical values and indicate that these loci might play a very important role in the application of DNA reports in the courts of justice. The studied population showed a relatively closer genetic affinity with Newar, Kathmandu, and Han Chinese populations compared with the South and West Indian populations. The outcomes of this study will enrich the STR database of the Indian population and this is the first global report on genetic diversity in the Meitei community of Manipur, India, at 20 autosomal STR genetic markers.